Fish-borne parasitic zoonosis in lower Mekong basin countries: Review - Nithikathkul, Choosak; Sujayanont, Patcharawan; Phyo Myint, Ei Ei; Sereemaspun, Amornpun x; Suancharoen, Pacharamon; Phalee, Anawat; Noradee, Sutthisak; Chuenkomol, Satthakarn (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2021)
Fish borne parasitic infections have been important public health problems in many parts of the world, particularly in countries of lower Mekong regions ie; Thailand, Lao People’s Democratic Republic (Lao PDR), Vietnam, Cambodia and Myanmar. Currently, many reports indicate that metacercariae of pathogenic trematodes are found in freshwater fish commonly small liver fluke, Opisthorchis viverrini; minute intestinal flukes (MIF); family of Heterophyidae. In Thailand, the epicenter of this disease is located in northeast region, where high a prevalence of opisthorchiasis coexists with a high incidence of cholangiocarcinoma (CHCA), a major primary carcinoma of the liver with a very poor prognosis. fish-borne trematode metacercariae are found in a variety of fish species, relating to carcinogenic liver fluke and minute intestinal flukes. This review aimed to summarized about the association of fish species (second intermediate Host) and metacercariae species in lower Mekong basin countries. In addition, this review might provide evidence leading to improved public health awareness for surveillance and control of FBT contamination and also contribute to filling the gap of information necessary for the control and prevention of fish borne trematode zoonotic infections in the lower Mekong region countries.